Adaptive Management Self-assessment tool - and mercy Corps (Mercy Corps, 2016)
The Adaptive Management self-assessment tool has been designed to help teams assess the extent to which they have a supportive environment for adaptive management within their country program. The self-assessment tool helps you think about five different areas that have been identified as important for supporting adaptive management: 1. Culture & leadership 2. Dynamic teams 3. Appropriate analysis 4. Responsive implementation & operations 5. Enabling environment (for example donor funding and relationships)